Kurikulum Katekisasi Trinitas Sebagai Kajian atas Kurikulum Katekisasi Kristosentris - Abet Nego, Peter (APOSTOLOS, 2025)
This article critically evaluates the Christocentric catechetical curriculum widely used in the Indonesian Christian Church (GKI), highlighting its neglect of the Trinitarian dimension. Through a combination of literature review and quantitative survey among teenage catechumens from two congregations, this study identifies a lack of integration of the Holy Spirit's role and the relational dynamics within the Trinity. The results suggest that the current curriculum contributes to fragmented theological understanding among adolescents. Drawing from Trinitarian theology, educational theory, and adolescent development, the article proposes a renewed curriculum model that centers the doctrine of the Trinity throughout all thematic teachings. This model emphasizes relational spirituality and introduces theological reflection that resonates with the lived faith experiences of adolescents. Ultimately, the article argues that catechesis must not only convey doctrine but also foster transformative encounters with the Triune God. A standardized yet contextually flexible synodal curriculum is recommended to ensure consistency and relevance.